Evaluation for effect of hypothermia on the disposition of 4‐nitrophenol in rats by in‐vitro metabolism study and rat liver perfusion system. (20th August 2013) - Miyamoto, Hirotaka; Matsueda, Satoshi; Komori, Kotaro; Fumoto, Shintaro; Nakashima, Mikiro; Yoshikawa, Naoki; Hirata, Haruna; Shimokawa, Kenta; Ohwaki, Yuichi; Nishida, Koyo
Abstract: Objectives: The aim of this study was to evaluate the effect of hypothermia on the in‐vivo pharmacokinetics of 4‐nitrophenol (4NP) using rat liver homogenate and rat liver perfusion system. Methods: Rat liver homogenate was incubated with 4NP, which is mainly metabolized by cytochrome P450 2E1, at 37, 34, 32 or 28°C. The Michaelis constant (Km ) and maximum elimination velocity (Vmax ) of 4NP were calculated by a Hanes–Woolf plot. The hepatic extraction ratio (Eh ) of 4NP was evaluated in a rat liver perfusion study at 37, 34, 32 or 28°C. Moreover, the plasma concentration profiles of 4NP after its intravenous (i.v.) administration to rats were analysed by the moment theory and were compared with in‐vitro parameters. Key findings: While the Km of 4NP was not changed, the Vmax and Eh were reduced at low temperatures. The plasma concentrations of 4NP after its i.v. administration to rats were significantly increased at 28°C. Conclusion: Changes in the pharmacokinetics of 4NP under hypothermic conditions were caused by alterations in Vmax and Eh . We may be able to predict the disposition of a drug by in‐vitro studies.